Ethnicity and older adults in the criminal justice system: a brief report from a nominal group - Mulligan, Lee (The journal of forensic psychiatry & psychology, 2025)
Older adults from UK minority ethnic backgrounds face increased marginalisation and inequalities within prison settings compared to the general prison population. Understanding the health and social care needs of people from minority ethnic backgrounds is essential to ensure equivalency of care, however, little research exists. This paper aims to explore the needs of older prisoners from minority ethnic backgrounds from the perspectives of multidisciplinary professionals. A nominal group discussion was conducted with 13 professionals with experience of supporting older prisoners from minority ethnic backgrounds. Six key themes were identified: 1) barriers to communication; 2) relationships with prison staff; 3) health competence; 4) stigma; 5) importance of family and spirituality; and 6) data collection and research. There was a consensus that the needs of older prisoners from minority ethnic backgrounds are complex and may not be adequately met in prison. Barriers faced by people from minority ethnic backgrounds include communication difficulties, a lack of diversity and cultural competence within the prison workforce, and stigma around seeking mental health support. Recommended solutions included greater collaboration with specialist community organisations, consideration of the composition and training of prison staff, and facilitation of family and spiritual support. The needs of older prisoners from minority ethnic backgrounds are unique and must be addressed in national policy.